1993
DOI: 10.1111/j.1365-2249.1993.tb05891.x
|View full text |Cite
|
Sign up to set email alerts
|

Defective IL-6 secretion in HIV-infected haemophilia patients

Abstract: SUMMARY To study the role of IL‐6 in HIV‐induced B cell defects, in vitro B cell responses and IL‐6 secretion were determined simultaneously in 67 haemophilia patients, Twenty‐three palients were HIV (Group 1). 27 HIV+ stage CDC II, III (Group 2). and 17 vi‐ere HIV4 stage CDC IV (Group 3). Pokeweed mitogen (PWM) was used forTeelI‐dependent and Staphylococcus aureus Cowan 1 (SAC I) for T cell‐independent B cell stimulalion. B cell differentiation was assessed in a reverse haemolytic plaque assay and by ELISA de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“… 1–3 During 30 years of follow-up, we observed that patients developed autoantibodies against CD4 + T lymphocytes, alloantibodies against HLA, autoantibodies against IgG and Fab, CD4 helper cell defects, cytokine abnormalities, macrophage and CD4 + lymphocyte dysfunctions associated with surface gp120-complement complexes, increased soluble Fas plasma levels, and apoptotic and nonapoptotic CD4 + T-cell depletion; during highly active antiretroviral therapy (HAART), they had decreasing sCD30 plasma levels and increasing dendritic cells (DC) and regulatory T-cell (Treg) blood levels. 1–14 Interestingly, long-term HIV + hemophilia patients and HIV − hemophilia patients showed four and two times as many activated CD3 + CD8 + DR + T lymphocytes in the blood, respectively, compared with healthy controls tested in parallel. 4 In a recently published manuscript, 4 we speculated that HIV − hemophilia patients might have an increased cytotoxic T-cell response because they were stimulated by clotting factor preparations, inactivated virus particles contaminating the clotting factor preparations, and chronic virus infections acquired in the era before virus inactivation of clotting factor preparations was practicable.…”
Section: Introductionmentioning
confidence: 99%
“… 1–3 During 30 years of follow-up, we observed that patients developed autoantibodies against CD4 + T lymphocytes, alloantibodies against HLA, autoantibodies against IgG and Fab, CD4 helper cell defects, cytokine abnormalities, macrophage and CD4 + lymphocyte dysfunctions associated with surface gp120-complement complexes, increased soluble Fas plasma levels, and apoptotic and nonapoptotic CD4 + T-cell depletion; during highly active antiretroviral therapy (HAART), they had decreasing sCD30 plasma levels and increasing dendritic cells (DC) and regulatory T-cell (Treg) blood levels. 1–14 Interestingly, long-term HIV + hemophilia patients and HIV − hemophilia patients showed four and two times as many activated CD3 + CD8 + DR + T lymphocytes in the blood, respectively, compared with healthy controls tested in parallel. 4 In a recently published manuscript, 4 we speculated that HIV − hemophilia patients might have an increased cytotoxic T-cell response because they were stimulated by clotting factor preparations, inactivated virus particles contaminating the clotting factor preparations, and chronic virus infections acquired in the era before virus inactivation of clotting factor preparations was practicable.…”
Section: Introductionmentioning
confidence: 99%